NURSES’ KNOWLEDGE AND PRACTICES TOWARD PREVENTION OF CATHETER-ASSOCIATED URINARY TRACT INFECTION AT KING ABDULAZIZ UNIVERSITY HOSPITAL - Algarni, Salha Salem; Sofar, Dr. Samah Sofar Sofar; Wazqar, Dr. Dhuha Youssef (Journal of Health, Medicine and Nursing, 2019)
Purpose: Urinary catheterization is one of the most common procedures performed in hospitals especially in intensive care units. The urinary catheter is considered as a single biggest risk factor for acquired urinary tract infections (UTIs), and more than 80% of all acquired UTIs are attributable to catheter use. The purpose of this study was to assess nurses' knowledge and practices toward prevention ofCAUTI at King Abdulaziz University Hospital (KAAUH). Materials and method: A cross-section, correlational study was conducted with a convenience sample of 137 nurses recruited from medical and intensive care units at KAAUH in Jeddah, Saudi Arabia. Knowledge and Practices Questionnaire was completed by participants. It included two parts: Part I: Socio-Demographic Questionnaire. Part II: Level of Knowledge and Extent of Practices Questionnaire. Data collection was carried out from November 2017 to January 2018. Data were analyzed using the SPSS version 22. Findings: The study findings revealed that more than half of nurses (62.77%) had a low level of knowledge and 83.94% of nurses had a poor level of practices. While 16.1% of nurses had a good level of practices. There was no significant relation between nurses' knowledge and practice toward CAUTI prevention. While there was a significant relation between nurses' knowledge and age and there was a significant relation between nurses' practices and current unit. Unique contribution to practice and policy: Further studies need to investigate the barrier affecting nurses' knowledge, attitude and practice regarding CAUTI prevention. Nurses should be trained regularly in CAUTI prevention, also hospital administration in Saudi hospitals should make every effort to include CAUTI prevention in their high priority list.